STANDARISASI GLOBAL HALAL DANDILEMATISASI REGULASI NASIONAL: TELAAHHUKUM ISLAM TERHADAP SERTIFIKASI HALALINDONESIA DALAM KONTEKS PASAR GLOBAL - Andi Rezal Juhari; Kurniati Kurniati; A. Qadir Gassing (JOSH: Journal of Sharia, 2026)
This study aims to analyze the dynamics of global halal standardization and its influence on halal certification regulations in Indonesia, as well as to examine the basis for their harmonization through a maqāṣid al-syarī‘ah approach. This study employs a normative juridical approach with library research methods by tracing and qualitatively analyzing legal documents (Law No. 33 of 2014 concerning Halal Product Assurance along with its implementing regulations), global halal standards, and related scientific literature. The results indicate that global halal standards develop through networks of state actors and transnational institutions; however, they remain fragmented due to differences in authorities, audit procedures, economic-political interests, and jurisprudential differences (ikhtilaf). Indonesia implements a mandatory halal certification that emphasizes regulatory sovereignty and precaution in the supply chain, yet faces a dilemma when export products still require re-certification in destination countries. The issue of mutual recognition demonstrates that certificate recognition is not merely technical, but also normative due to its connection with the legitimacy of fatwa authorities. This study recommends a maqāṣid-based selective convergence through strengthening halal standardization diplomacy, increasing halal infrastructure capacity (Halal Inspection Agencies, auditors, laboratories), and formulating transparent and proportionate mutual recognition schemes to be compatible with the global market without compromising sharia certainty.